2012
DOI: 10.1021/jp211041m
|View full text |Cite
|
Sign up to set email alerts
|

Effective Surface Charge Density Determines the Electrostatic Attraction between Nanoparticles and Cells

Abstract: ABSTRACT:We examine the origin of the electrostatic attraction between nanoparticle (NP) and cells by synthesizing a NP array with a continuous change in surface charge density (SCD). This attraction does not show a linear and continuous change, but a sharp increase as the positive SCD increases. The results of zeta potential measurements of the naked and protein bound NPs reveal that excessive charges on surface ligands are partially shielded, and the noncovalent protein bindings do not influence NP−cell elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 46 publications
2
81
0
Order By: Relevance
“…22,33 Bannunah et al found that both positively and negatively charged blue aminated latex nanoparticles (50 nm) and orange 32 The cellular internalization of positively charged nanoparticles in Caco-2 cell monolayers was significantly higher than that of negatively charged nanoparticles, 32 which was also true for many other cells. 34 However, negatively charged nanoparticles taken up into plant tissues were more efficiently transported across cell monolayers than positively charged nanoparticles. 32 In addition, the uptake of positively charged quantum dots (QDs) was 10 times faster than that of negatively charged QDs in poplar plants after 11 days of incubation due to their electrostatic attraction with the negatively charged root cell wall and cell membrane.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…22,33 Bannunah et al found that both positively and negatively charged blue aminated latex nanoparticles (50 nm) and orange 32 The cellular internalization of positively charged nanoparticles in Caco-2 cell monolayers was significantly higher than that of negatively charged nanoparticles, 32 which was also true for many other cells. 34 However, negatively charged nanoparticles taken up into plant tissues were more efficiently transported across cell monolayers than positively charged nanoparticles. 32 In addition, the uptake of positively charged quantum dots (QDs) was 10 times faster than that of negatively charged QDs in poplar plants after 11 days of incubation due to their electrostatic attraction with the negatively charged root cell wall and cell membrane.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Moreover, it greatly influences the interaction with cell membrane and the internalization pathways of NDs into cells [166]. The control of surface terminations allows a tuning of NDs surface charge in suspension from negative to positive versus pH.…”
Section: Surface Graphitization Of Nanodiamondsmentioning
confidence: 99%
“…The control of ND surface charge is essential for drug or biological moieties adsorption [27,29,31] it can also play a major role in internalization pathways and interactions with negatively charged cell membrane [166]. In this part, the surface reactivity of modified NDs will be discussed.…”
Section: Colloidal Properties Of Modified Nanodiamondsmentioning
confidence: 99%
“…35 Positively charged NPs bind strongly to serum components in the blood via noncovalent interactions with proteins and electrostatic interactions with the cell surface. [36][37][38] Furthermore, these positively charged NPs can be easily taken up by nonphagocytic cells and cause more disruption of the membrane integrity and lysosomal and mitochondrial damage than their negatively charged counterparts. [39][40][41][42] Positively charged Au NPs, therefore, display high uptake in the liver.…”
Section: Introductionmentioning
confidence: 99%